2022
DOI: 10.1101/2022.07.19.500679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA-mRNA networks are dysregulated in opioid use disorder postmortem brain: further evidence for opioid-induced neurovascular alterations

Abstract: To understand mechanisms and identify potential targets for intervention in the current crisis of opioid use disorder (OUD), postmortem brains represent an under-utilized resource. To refine previously reported gene signatures of neurobiological alterations in OUD from the dorsolateral prefrontal cortex (Brodmann Area 9, BA9), we explored the role of microRNAs (miRNA) as powerful epigenetic regulators of gene function. Building on the growing appreciation that miRNAs can cross the blood-brain barrier, we carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The discovery of ncRNAs has revolutionized our understanding of regulation of gene expression and opened new avenues for therapeutic intervention ( Kopp & Mendell, 2018 ). Many diseases, including cancer and neurological disorders, have been linked to dysregulation of ncRNA expression or function ( Grimm et al, 2022 , Yao et al, 2019 ). Though research on ncRNAs could be used to develop new diagnostic and therapeutic strategies, this avenue remains mostly unexplored regarding underlying factors that drive OIH.…”
Section: Non-coding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of ncRNAs has revolutionized our understanding of regulation of gene expression and opened new avenues for therapeutic intervention ( Kopp & Mendell, 2018 ). Many diseases, including cancer and neurological disorders, have been linked to dysregulation of ncRNA expression or function ( Grimm et al, 2022 , Yao et al, 2019 ). Though research on ncRNAs could be used to develop new diagnostic and therapeutic strategies, this avenue remains mostly unexplored regarding underlying factors that drive OIH.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Further, a study on postmortem brain and blood tissue from people with OUD revealed miRNA alterations associated with changes in endothelial cell function and tube development. Notably, miR-92a-3p was upregulated and miR-29a downregulated in the brain, both acting via the p38 MAPK signaling pathway ( Grimm et al, 2022 ). p38 MAPK has been highly correlated with various pain states ( Anand et al, 2011 , Crown et al, 2008 , Mai et al, 2020 ), so it is possible that differential expression of p38 MAPK associated miRNAs after prolonged opioid usage could potentiate pain and lead to OIH.…”
Section: Human Studiesmentioning
confidence: 99%
“…Only one such study has been performed with human samples, and this is likely due to the challenges of collecting blood and postmortem samples in a timely manner. Grimm et al reported the correspondence of frontal cortex brain and blood miRNA levels in postmortem human samples from OUD subjects and observed a large overlap in miRNA expression [65]. Of the miRNA profile measured in the BA9 region, the authors observed differential expression of hsa-miR-10b-5p, hsa-miR-337-3p, has-miR-340-5, hsa-miR-376a-3p, hsa-miR-376b-3p, hsa-miR-379-5p, hsa-miR-486-3p, hsa-miR-495-3p, and hsa-miR-758-3p [65], which were all dysregulated in the OFC of heroin-exposed rats in the current study.…”
Section: Advances In Drug and Alcohol Researchmentioning
confidence: 99%
“…Grimm et al reported the correspondence of frontal cortex brain and blood miRNA levels in postmortem human samples from OUD subjects and observed a large overlap in miRNA expression [65]. Of the miRNA profile measured in the BA9 region, the authors observed differential expression of hsa-miR-10b-5p, hsa-miR-337-3p, has-miR-340-5, hsa-miR-376a-3p, hsa-miR-376b-3p, hsa-miR-379-5p, hsa-miR-486-3p, hsa-miR-495-3p, and hsa-miR-758-3p [65], which were all dysregulated in the OFC of heroin-exposed rats in the current study. Investigation into the relationship between drug exposure and regulation of brain miRNAs that can also be detected in the periphery can be accomplished easily with rodent models of self-administration but has yet to be done.…”
Section: Advances In Drug and Alcohol Researchmentioning
confidence: 99%
“…The dorsolateral prefrontal cortex (DLPFC) and nucleus accumbens (NAc) are key brain regions involved in cognitive, mood, and reward alterations in OUD [9][10][11]. Recent human postmortem brain studies from us [2,3] and others [4,6,12,13] reported a potential interplay between proinflammatory and synaptic remodeling in DLPFC and NAc in OUD. Moreover, we recently implicated circadian rhythm regulation of neuroinflammatory, neurovascular, and neurotransmission (e.g., dopaminergic, GABAergic, and opioidergic signaling) in DLPFC and NAc of OUD subjects [2,3].…”
Section: Introductionmentioning
confidence: 99%